2004
DOI: 10.1007/bf03218444
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic velocity and absorption measurements in an aqueous solution of poly(sodium 4-styrenesulfonate)

Abstract: Both the ultrasonic velocity at 3 MHz and the absorption coefficient in the frequency range from 0.2 to 2 MHz were measured for aqueous solutions of poly(sodium 4-styrenesulfonate) over the concentration range from 5 to 25% (by weight). The pulse echo overlap method was employed to measure the ultrasonic velocity over the temperature range from 10 to 90 o C; the high-Q ultrasonic resonator method was used for the measurement of the absorption coefficient at 20 o C. The velocities exhibited their maximum values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It was reported that ultrasonic adsorption to polymeric medium was evaluated by absorption coefficients, sound velocities and viscosity, for different nonionic and ionic polymer solutions, such as polyethylene glycol (PEG), polyvinyl alcohol (PVA) and PAA, at high frequencies of 2-130 MHz. [14][15][16][17][18] However, no results for US using lower frequencies have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that ultrasonic adsorption to polymeric medium was evaluated by absorption coefficients, sound velocities and viscosity, for different nonionic and ionic polymer solutions, such as polyethylene glycol (PEG), polyvinyl alcohol (PVA) and PAA, at high frequencies of 2-130 MHz. [14][15][16][17][18] However, no results for US using lower frequencies have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the obtained measurement quality, pushing the resolution of current ultrasonic velocimeters to 10 −7 , such measurements are used more and more often, not only for fundamental studies in physical chemistry [12][13][14][15][16][17][18], biophysics and biochemistry [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], but also for numerous technical applications, e.g. in chemical engineering.…”
Section: Introductionmentioning
confidence: 99%